2018
DOI: 10.17827/aktd.339137
|View full text |Cite
|
Sign up to set email alerts
|

Ruhsal Bozukluklarda Uyku

Abstract: Sleep is a physiological need and is related with learning, memory and mood regulation. Change in sleep quality and quantity is one of the basic complaints in most of mental disorders. Sleep disturbances are observed in many different disorders such as depression, bipolar disorder, schizophrenia, drug dependence and anxiety disorders and significantly influences disease course. Sleep disorders which are known to have negative effects on clinical outcome, treatment response and quality of life in mental disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Literatür incelendiğinde, depresyonun uyku sorunlarına yol açabileceği gib, uyku sorunlarının da depresyona neden olabileceği veya eşlik edebileceği görülmektedir. 33 Çalışmamızda, katılımcılarda pandemi döneminde pandemi öncesine göre algılanan genel sağlık durumunun kötüleşme sıklığı %37,2'dir. 65 ülkeden 3.550 katılımcıda yapılan bir çalışmaya göre, pandemi kronik hastalığı olan bireylerin %48,5'inin algılanan sağlık durumunu olumsuz etkilemiştir.…”
Section: Discussionunclassified
“…Literatür incelendiğinde, depresyonun uyku sorunlarına yol açabileceği gib, uyku sorunlarının da depresyona neden olabileceği veya eşlik edebileceği görülmektedir. 33 Çalışmamızda, katılımcılarda pandemi döneminde pandemi öncesine göre algılanan genel sağlık durumunun kötüleşme sıklığı %37,2'dir. 65 ülkeden 3.550 katılımcıda yapılan bir çalışmaya göre, pandemi kronik hastalığı olan bireylerin %48,5'inin algılanan sağlık durumunu olumsuz etkilemiştir.…”
Section: Discussionunclassified
“…It has been reported that diagnosed disease is a risk factor for mental issues (Engidaw et al , 2020). Similarly, Uzunçakmak (2018) also reported that compared to individuals without a diagnosed disease, those with a diagnosed illness had 2.25 times as many psychological issues (Keskin and Tamam, 2018). Our findings point to the importance of evaluating and supporting students with a diagnosed illness in terms of mental health.…”
Section: Discussionmentioning
confidence: 99%